Evolution of Multiple Sclerosis Lesions on Serial Contrast-Enhanced T1-Weighted and Magnetization-Transfer MR Images - Rovira, Alex; Alonso, Juli; Cucurella, Gracia; Nos, Carlos; Tintoré, Mar; Pedraza, Salvador; Rio, Jordi; Montalban, Xavier (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Magnetization-transfer imaging is a technique that could provide indirect evidence of the characteristics of multiple sclerosis (MS) lesions. The purpose of this work was to study the evolution of MS lesions on T1-weighted MR images over time and to investigate changes in magnetization-transfer ratio (MTR) values of MS lesions with different initial appearances on contrast-enhanced T1-weighted images.METHODS: Eleven patients with relapsing-remitting MS were studied with MR imaging. The MTRs were calculated for 47 lesions that had been classified according to their appearance on contrast-enhanced T1-weighted images. Each patient was examined at four time points over a 1-year period. The MTR changes observed in the selected lesions were compared with their initial T1-weighted appearance.RESULTS: The lowest MTR values were initially found in hypointense nonenhancing lesions and in ring-enhancing lesions, with both types showing a hypointense center. Changes in MTR values were more dynamic and reversible in ring-enhancing than in hypointense nonenhancing plaques. Nodular-enhancing lesions had slightly lower initial MTRs than did isointense nonenhancing lesions.CONCLUSION: The absence or presence of contrast uptake may indicate a different pathologic basis for hypointense MS lesions on T1-weighted MR images. These differences should be kept in mind when considering T1 lesion load as a surrogate marker of disability in MS.